Central Bank Boards Around the World : Why Does Membership Size Differ? - Berger, Helge; Lybek, Tonny; Nitsch, Volker (Washington, D.C. : International Monetary Fund, 2006)
This paper analyzes empirically differences in the size of central bank boards across countries. Defining a board as the body that changes monetary instruments to achieve a specified target, we discuss the possible determinants of a board's size. The empirical relevance of these factors is examined using a new dataset that covers the de jure membership size of 84 central bank boards at the end of 2003. We find that larger and more heterogeneous countries, countries with stronger democratic institutions, countries with floating exchange rate regimes, and independent central banks with more staff tend to have larger boards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet